Evaluation of Greenship GBCI Appropriate Site Development in Poltekkes Riau Tower - Kusumah, Dadang Puja; Tela, I Nengah; Haryani, Haryani (Universitas Bandar Lampung (UBL), 2025)
Greenship certification system in Indonesia which is developed by the Green Building Council Indonesia (GBCI), serves as an assessment tool. This study evaluates the implementation of the ASD (Site Accessibility and Transportation) category under Greenship for the Riau Polytechnic Tower from an architectural perspective, focusing on gaps in site planning, passive design strategies, and place-making. A mixed-method approach was employed, combining quantitative scoring and qualitative analysis to assess the architect’s role in integrating environmental principles into the building completed in 2022. The research applied a combined strategy of quantitative data evaluation and qualitative analysis to validate findings objectively, analyzing 8 ASD criteria through field observations, document reviews, and as-built drawing assessments. Results revealed the building scored only 5 out of 17 points (29.4%) in the ASD category, meeting criteria such as basic green area (ASD-P), site selection (ASD-1), community accessibility (ASD-2), public transportation (ASD-3), and microclimate management (ASD-6). However, bicycle facilities, landscaping, and stormwater management criteria remained unmet. These findings underscore the necessity for enhanced land-based green design and improved infrastructure integration in educational buildings. Recommendations are provided to strengthen green building implementation in high-rise educational facilities, emphasizing the importance of architectural narratives in advancing sustainability, beyond mere technical compliance.